Luckiest Girl Alive - Knoll, Jessica (Thorndike, Maine : Center Point Large Print, 2015)
"A young woman strives to create the perfect life--husband, home, career--until a violent incident from her past threatens to unravel everything and expose her most shocking secret of all"--
Keywords: Young women -- Fiction -- New York (State); Women journalists -- Fiction; Life change events -- Fiction; Large type books